The Inhibitory Activity and Kinetics of α-Glucosidase by Toona sinensis Stem Bark Extracts - Melati Devina Gustini Wirastuti; Syamsul Falah; Syaefudin (IPB University, 2022)
Research on the potential of the Surian tree (Toona sinensis) for medicine has been carried out, especially for the leaves. However, the bark section has not been done much. This study aimed to determine the inhibitory activity of -glucosidase and IC50 extract as well as the fraction of surian bark as antidiabetic in vitro. The reflux method with water at 90oC and maceration using 70% ethanol at room temperature was carried out to obtain aqueous and ethanol extracts. Furthermore, the ethanol extract was fractionated successively using n-hexane, diethyl ether, and ethyl acetate. Phytochemical screening test showed that the aqueous extract contained flavonoids, saponins, and tannins. Meanwhile, the 70% ethanol extract and its fraction showed terpenoid content, in addition to flavonoid compounds, saponins, and tannins. The best -glucosidase inhibition was shown by 70% ethanol extract, which was 70.45 ppm followed by ethyl acetate fraction, n-hexane fraction, diethyl ether fraction, and water extract of surian bark with values of 81.96 g/mL, 98.76 g/mL, respectively. , 140.25 g/mL, and 242.85 g/mL. Kinetics of -glucosidase inhibition showed that 70% ethanol extract of surian bark inhibited through a non-competitive inhibition mechanism, characterized by a decrease in Vmax from 8.29x10-3 mM/min to 1.65x10-3 mM/min and a decrease in Km from 0.17 mM to 0.03 mM.